THU0151 Five-year Progression of Left Ventricular Diastolic Dysfunction in Patients with Rheumatoid Arthritis Compared to the General Population. (9th June 2015) - Davis, J.M.; Lin, G.; Oh, J.K.; Crowson, C.S.; Achenbach, S.J.; Therneau, T.M.; Matteson, E.L.; Rodeheffer, R.J.; Gabriel, S.E.
Abstract : Background: Patients with rheumatoid arthritis (RA) have increased risk of heart failure not explained by traditional cardiovascular risk factors. Even patients without clinical heart disease have a high prevalence of left ventricular (LV) diastolic dysfunction. 1, 2 However, little is known about the progression of LV diastolic dysfunction over time in patients with RA relative to the general population. Objectives: The objective of this study was to evaluate longitudinal changes in echocardiographic parameters of LV function in subjects with RA compared to the general population. Methods: A prospective longitudinal study of a population-based cohort of subjects with RA as well as a population-based cohort of subjects without RA (non-RA) from the same underlying community was performed, using the resources of the Rochester Epidemiology Project. Patients were seen at study baseline and approximately 4 or 5 years later for the non-RA or RA cohorts, respectively. At baseline and follow-up, each subject underwent examination by a registered diagnostic cardiac sonographer using pulse wave and tissue Doppler echocardiography, according to a standardized research protocol. Structural and hemodynamic parameters were analyzed according to guidelines and criteria of the American Society of Echocardiography. Age- and sex-adjusted linear regression models were used to test for differences between the RA and non-RA cohorts in the estimated annualized rates of change for individual echocardiographic parameters. Results: A total of 160 subjects with RA and 1391 non-RA subjects were included in this study. The mean age of the RA cohort was younger than the non-RA cohort (58.5 vs. 61.1 yrs., p=0.001). The percentage of females was higher in the RA than non-RA cohort (76.3% vs. 50.6%, p<0.001). Longitudinal changes in LV structure and function occurred in both the non-RA and RA cohorts. The main finding was the significant acceleration of the A velocity over time among the subjects with RA compared to non-RA subjects (age- and sex-adjusted parameter estimate: 0.030; p<0.0001). Correspondingly, the mean E/A ratio decreased faster in the RA compared to non-RA subjects (parameter estimate: -0.096, p<0.0001). The e' velocity decreased and the E/e' ratio increased over time in both cohorts, but these changes were not significantly different between the cohorts. Conclusions: The findings of this study suggest that diastolic dysfunction progresses more rapidly over 5 years in patients with RA compared to members of the general population. Further research into the mechanisms of myocardial disease in these patients and their relationships with disease activity and treatment is warranted. References: Liang KP et al. Increased prevalence of diastolic dysfunction in rheumatoid arthritis. Ann Rheum Dis. 2010;69:1665-70. Aslam F et al. Diastolic dysfunction in rheumatoid arthritis: a meta-analysis and systematic review. Arthritis Care Res (Hoboken). 2013 Apr;65(4):534-43. Disclosure of Interest: None declared